Levels of rna for TNF-α and receptors during the prereplicative period of liver regeneration - Obolenskaya, M.Yu.; Bernauer, H.; Tran-Thi, T.-A.; Decker, K. (Биополимеры и клетка, 1994)
During the prereplicative period of liver regeneration the changes of the tnRNA contents for tumor necrosis factor-α (TNF-α) and its receptors were examined in total liver RNA with the help of reverse transcriptase-polymera.se chain reaction (RT-PCR) and compared with those after sham operation or stimulation with lipopolysaccharide (LPS). In regenerating liver all the changes are nearly synchronous with a slight delay (or the TNF receptor RNAs. The mRNA levels reach their maximum at 1–3 h after operation and exceed the values for intact animals about ten-fold. The corresponding changes induced by sham operation are quantitatively less than those in the regenerating liver and manifest themselves at the end of the prereplicative period. LPS stimulation induced an increase of TNF-α and TNF receptor production comparable with during regeneration. Analysis of the expression of the 55 kDa TNF receptor revealed qualitative changes, e. g. an increased polyadenylation and an imbalance between the amplification of the whole molecule and its 5'-terminal half pointing to as yet unidentified changes at the 3' end of the molecule.